Two-component UV-curable acrylic-epoxy resin film and preparation method and application thereof
Through the technology of curing acrylic-epoxy resin film with two-component ultraviolet light, combined with cinnamic acid modification and dual curing system, the problem of insufficient peel strength between copper foil and glass fiber in traditional PCB boards is solved, and the film with high peel strength and low dielectric loss is achieved, meeting the needs of high-frequency signal transmission.
Patent Information
- Application Number
- CN202310355317.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-04-06
AI Technical Summary
During the use of traditional PCB board epoxy substrates, the peel strength between the copper foil and the glass fiber is limited, making it difficult to meet the needs of high-frequency signal transmission.
A solvent-free semi-cured adhesive film was prepared by two-component ultraviolet light curing acrylic-epoxy resin film, and copolymerized by cinnamic acid and end-hydroxybisphenol A-type epoxy resin, combined with ultraviolet light and high-temperature dual curing system, thereby improving the adhesion strength between the copper foil and the adhesive film.
The adhesive film with high peel strength and low dielectric loss is achieved, which meets the needs of high-frequency signal transmission and reduces environmental pollution through solvent-free production.
Smart Images

Figure BDA0004163104540000051 
Figure BDA0004163104540000061 
Figure BDA0004163104540000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer blending and composite materials, and more specifically to a two-component ultraviolet light-cured acrylic acid-epoxy resin adhesive film and a preparation method and application thereof. Background Art
[0002] Communication technology has gone through 40 years of development from the first generation to the fifth generation. Among them, the fifth generation (5G) and sixth generation (6G) mobile communication technology have the characteristics of ultra-high signal transmission speed (10Ghps) and ultra-low latency (<1ms). The development of 5G and 6G mobile communication technology is highly dependent on new materials, which depends on the close relationship between the dielectric constant and dielectric loss of the printed circuit board (PCB) when the signal is transmitted in the PCB. Therefore, the selection of resin-based materials with low dielectric loss and high insulation is the key to ensure efficient signal transmission.
[0003] At present, with the rapid upgrading of production technology and environmental protection requirements, the traditional solvent-based bisphenol A epoxy adhesive material for PCB boards has gradually been replaced by solvent-free preparation of low-dielectric epoxy resin-based adhesive films. Whether it is the configuration of the resin system or the use of PCB substrates, efficiency and environmental safety will be significantly improved. After nearly ten years of research, Professor Li Huilu's team at Xi'an University of Science and Technology has achieved the localization of solvent-free epoxy resin-based adhesive films. The formula and process of solvent-free preparation of epoxy resin systems and semi-cured adhesive films directly determine the overall technical level of downstream PCB boards.
[0004] The traditional epoxy substrate of PCB board is based on liquid epoxy resin combined with curing agent, which is coated on glass fiber cloth for pressing. Due to the presence of glass fiber cloth, the peel strength between copper foil and glass fiber will be greatly tested. Summary of the invention
[0005] In view of the above problems, the present invention provides a two-component UV-curable acrylic-epoxy resin adhesive film, a preparation method and an application thereof, and prepares a solvent-free semi-cured adhesive film.
[0006] The first object of the present invention is to provide a method for preparing a two-component UV-curable acrylic-epoxy resin film, which is prepared according to the following steps:
[0007] Step 1, using an alkali agent as a catalyst, a hydroxyl-terminated epoxy resin and an epoxy diluent undergo a chemical ring-opening reaction to obtain a ring-opened epoxy resin glue solution;
[0008] Step 2, adding 3-phenyl-2-acrylic acid to the ring-opened epoxy resin prepared in step 1 to carry out an esterification reaction to obtain a cinnamic acid-modified epoxy resin glue;
[0009] Step 3, adding an ultraviolet light initiator, an epoxy curing agent, an accelerator and a leveling agent to the cinnamic acid-modified epoxy resin prepared in step 2, and mixing them evenly at room temperature in the dark to obtain a two-component cinnamic acid-modified epoxy prepolymer glue;
[0010] Step 4: Add the coupling agent and thermal conductive filler to the two-component cinnamic acid modified epoxy prepolymer prepared in step 3 and disperse them evenly to obtain a two-component UV-curable acrylic-epoxy resin composite adhesive solution, which is coated on a release film and cured under ultraviolet light to obtain a semi-cured two-component UV-curable acrylic-epoxy resin adhesive film.
[0011] Preferably, in step 1, the reaction temperature of the chemical ring-opening reaction is 60-75° C., and the reaction time is 1-2.5 h; wherein the mass ratio of the hydroxyl-terminated epoxy resin, the epoxy diluent, and the alkali agent is 45-75:25:0.1-1.5.
[0012] Preferably, in step 1, the alkaline agent is one of potassium hydroxide, barium hydroxide or sodium hydroxide.
[0013] Preferably, in step 2, the reaction temperature of the esterification reaction is 75-90°C, and the reaction time is 1.5-3h; wherein the molar ratio of the carboxyl group of 3-phenyl-2-acrylic acid to the epoxy group in the epoxy resin glue after ring opening is 0.15-0.55:1.
[0014] Preferably, in step 3, the mass ratio of the ultraviolet light initiator to the cinnamic acid modified epoxy resin glue is 0.06-0.1:1; the mass ratio of the epoxy curing agent to the cinnamic acid modified epoxy resin is 0.04-0.3:1; the mass ratio of the accelerator to the cinnamic acid modified epoxy resin is 0.01-0.05:1; the mass ratio of the leveling agent to the cinnamic acid modified epoxy resin is 0.001-0.003:1.
[0015] Preferably, in step 3, the ultraviolet light initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, the epoxy curing agent is bismaleimide, the accelerator is 2-ethyl-4-methylimidazole and the leveling agent is polyether-modified siloxane.
[0016] Preferably, in step 4, the mass ratio of the coupling agent, the thermal conductive filler, and the two-component cinnamic acid modified epoxy prepolymer is 1-3:55-75:25-45.
[0017] Preferably, the thermally conductive filler is a composite of silicon micropowder and aluminum oxide, and the mass ratio of silicon micropowder to aluminum oxide is 0.25-1:1;
[0018] The release film is a polyethylene glycol film.
[0019] The second object of the present invention is to provide a two-component UV-curable acrylic-epoxy resin film prepared by the above preparation method.
[0020] The third object of the present invention is to provide an application of the above two-component UV-curable acrylic-epoxy resin adhesive film in a PCB board, characterized in that after the two-component UV-curable acrylic-epoxy resin adhesive film is laminated and bonded to a copper foil, secondary high-temperature curing is performed to obtain a PCB board;
[0021] Among them, the secondary high-temperature curing temperature is 170-220°C, the curing time is 2h, and the press pressure is 5-10Mpa.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention copolymerizes cinnamic acid with terminal hydroxyl bisphenol A epoxy resin to introduce double-bonded organic molecules containing benzene rings into the molecular chain of bisphenol A. By adding ultraviolet light accelerator and epoxy curing agent, the terminal hydroxyl epoxy resin modified by cinnamic acid can be endowed with two functions: first, it can form a film quickly on the PET film under the action of ultraviolet light, and at high temperature (>120°C), the epoxy groups in the molecular chain can be secondary cured and bonded to the copper foil. In this way, by designing the temperature range of the dual curing system, a solvent-free semi-cured adhesive film can be prepared.
[0024] (2) Traditional adhesive films use diluents to achieve a high filler loading in the resin, and then heat to volatilize the diluent. At the same time, a portion of the epoxy resin is cured to a certain degree to reach a semi-cured state. The disadvantage is that environmental pollution and residual solvents will affect the performance. Compared with traditional adhesive films, the present invention prepares a low-viscosity two-component UV-curable phenyl acrylic acid-epoxy resin system and adhesive film, which has high peel strength and low dielectric loss characteristics. During the preparation process, the introduction of cinnamic acid solves the problem of film formation of the composite resin system; the resin system in the present invention has low viscosity, and the double bond group reaches a semi-cured film-forming state during UV curing, achieving solvent-free production, and can only carry out high-proportion filling of fillers.
[0025] (3) Compared with traditional epoxy resins and phenolic resins, the hydroxy-terminated epoxy resin modified by cinnamic acid in the present invention has the characteristics of good photosensitivity and high resin bonding strength under high-temperature curing. The dual-curing system can be used to design new high-performance resins.
[0026] (4) Compared with traditional solvent-based epoxy and acrylic resins, the cinnamic acid-modified epoxy film prepared by the present invention has better comprehensive performance under the action of thermal conductive filler and does not require equipment replacement, thus solving the problem of solvent-free development of high-performance polymer substrates at low cost.
[0027] (5) The cinnamic acid modified epoxy resin prepared by the present invention controls the molar ratio of the carboxyl group in the cinnamic acid to the epoxy group in the epoxy resin to be between 0.15 and 0.55 during the preparation process in order to ensure that a semi-cured film material that is not sticky can be formed after ultraviolet curing at room temperature, and the epoxy group in the semi-cured film material can have a strong adhesive force with the copper foil under high temperature curing conditions. If the epoxy group content is too low, the adhesive force with the copper foil will decrease, resulting in unsatisfactory product performance. If the epoxy group content is too high, the semi-cured film will become sticky, which is not conducive to processing. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The hydroxy-terminated bisphenol A epoxy resin used in the present invention was purchased from Hongchang Electronic Materials Co., Ltd. GEBR481A80 epoxy resin, and the linear epoxy diluent was the company's butyl glycidyl ether dilution type (GEKR115). The cinnamic acid was purchased from Wuhan Organic Materials Company.
[0030] The copper foil was purchased from Tongchuan Core Material Co., Ltd. with a thickness of 20-50 μm; the silicon micropowder was purchased from Xi'an Tianyuan Chemical Co., Ltd. with a particle size of 10-20 μm; and the aluminum oxide was purchased from Qinhuangdao Yinuo Company with a particle size of 15-20 μm.
[0031] Example 1
[0032] This embodiment provides a method for preparing a two-component UV-curable acrylic-epoxy resin film, comprising the following steps:
[0033] Step 1, using sodium hydroxide as a catalyst, weighing 0.1 g of sodium hydroxide and dissolving it in 10 mL of ethanol solution, adding the dissolved sodium hydroxide solution to a mixed solution of 45 g of hydroxyl-terminated epoxy resin and 25 g of epoxy diluent to carry out a chemical ring-opening reaction, the reaction temperature is 75° C., the reaction time is 2 hours, and the ring-opened bisphenol A epoxy resin glue is obtained;
[0034] Step 2, adding 7 g of 3-phenyl-2-acrylic acid (cinnamic acid) to 45 g of the ring-opened bisphenol A epoxy resin glue prepared in step 1 at room temperature, and then placing it in a heating jacket to heat up for esterification reaction, the reaction temperature is 75° C., the reaction time is 3 hours, and the cinnamic acid-modified bisphenol A epoxy resin glue is obtained;
[0035] Step 3, adding 3g of ultraviolet light initiator, 15g of epoxy curing agent, 0.5g of accelerator and 0.1g of leveling agent to 45g of the cinnamic acid-modified bisphenol A epoxy resin glue prepared in step 2 under a light-proof environment, and stirring at room temperature for 0.5 hour to obtain a two-component cinnamic acid-modified epoxy prepolymer glue that can be photocured and heat-cured;
[0036] Step 4: Add 2g of coupling agent to 25g of the two-component cinnamic acid modified epoxy prepolymer glue and disperse it at high speed for 5 minutes at a speed of 650rmp / min, and quickly add 75g of thermal conductive filler (the mass ratio of silicon micropowder and alumina is 0.5:1) to fully disperse it evenly to obtain a two-component UV-curable acrylic-epoxy resin composite. The two-component UV-curable acrylic-epoxy resin composite is coated on the release film by a coating apparatus (the coating parameters of the coating machine are: coating in the dipping tank, the coating speed is 0.5 m / min, the coating drying tunnel temperature is 90°C, and the drying tunnel length is 6 meters), and irradiate for 30s under ultraviolet light (290nm) for rapid curing and film formation, wherein the irradiation is carried out at room temperature to obtain a semi-cured bisphenol A film with uniform phase distribution. Its basic formula is shown in Table 1.
[0037] Table 1 Formula of two-component UV-curable acrylic-epoxy resin composite
[0038]
[0039]
[0040] Example 2
[0041] This embodiment provides a method for preparing a two-component UV-curable acrylic-epoxy resin film, using Formula 5 as the base resin formula, and its thermal conductivity after being matched with different fillers is shown in Table 2.
[0042] Specifically:
[0043] Step 1, weigh 0.3g of sodium hydroxide and dissolve it in 10mL of ethanol solution, add the dissolved sodium hydroxide solution into a mixed solution of 65g of terminal hydroxyl epoxy resin and 25g of epoxy diluent to carry out chemical ring-opening reaction, the reaction temperature is 75°C, the reaction time is 2 hours, and the ring-opened bisphenol A epoxy resin glue is obtained;
[0044] Step 2, adding 15 g of 3-phenyl-2-acrylic acid (cinnamic acid) to 65 g of the ring-opened bisphenol A epoxy resin glue obtained in step 1 at room temperature, and then placing it in a heating jacket to heat it for esterification reaction at a temperature of 75° C. for 3 hours to obtain a cinnamic acid-modified bisphenol A epoxy resin system;
[0045] Step 3, adding 5g of ultraviolet light initiator, 5g of epoxy curing agent, 0.5g of accelerator and 0.1g of leveling agent to 65g of cinnamic acid modified bisphenol A type epoxy resin glue prepared in step 2 under a light-proof environment, stirring at room temperature for 0.5 hour to obtain a two-component cinnamic acid modified epoxy prepolymer system that can be photocured and heat-cured;
[0046] Step 4: Add 2 g of coupling agent to 25 g of the prepared two-component cinnamic acid modified epoxy prepolymer glue and disperse it at high speed for 5 minutes at a speed of 650 rpm. Quickly add 75 g of weighed thermal conductive filler (silicon powder: alumina mass ratio of 1:1) and fully disperse it to obtain a two-component UV-curable acrylic-epoxy resin composite.
[0047] A 50% two-component UV-curable acrylic-epoxy resin composite was coated on a release film by a coating apparatus (the coating parameters of the coating machine were: coating in a dipping tank, a coating speed of 0.5 m / min, a coating drying tunnel temperature of 90°C, and a drying tunnel length of 6 m), and irradiated under ultraviolet light (290 nm) for 30 s for rapid curing to form a film, wherein the irradiation was carried out at room temperature to obtain a semi-cured bisphenol A film with uniform phase distribution.
[0048] Then, 50 g of the two-component UV-curable acrylic-epoxy resin composite was weighed and placed on a release film (the coating machine parameters were the same as those in Example 1) and irradiated with UV light (290 nm) at room temperature for 30 seconds for preliminary curing into a uniform semi-cured bisphenol A film.
[0049] After the film is formed, it is hot pressed at a high temperature of 180°C for 2 hours to obtain a flexible thermal conductive adhesive film. The thermal conductivity coefficient is shown in Table 2.
[0050] Example 3
[0051] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as that of Embodiment 2, except that the 75 g thermal conductive filler added in step 4 is composed of silicon powder and aluminum oxide in a mass ratio of 0.25:1.
[0052] Example 4
[0053] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as that of Embodiment 2, except that the 75 g thermal conductive filler added in step 4 is composed of silicon powder and aluminum oxide in a mass ratio of 0.5:1.
[0054] Example 5
[0055] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of two-component cinnamic acid modified epoxy prepolymer added is 35 g, the amount of thermal conductive filler added is 65 g, and the mass ratio of silicon micropowder to alumina is 1:1.
[0056] Example 6
[0057] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of two-component cinnamic acid modified epoxy prepolymer added is 35 g, the amount of thermal conductive filler added is 65 g, and the mass ratio of silicon micropowder to alumina is 0.25:1.
[0058] Example 7
[0059] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of two-component cinnamic acid modified epoxy prepolymer added is 35 g, the amount of thermal conductive filler added is 65 g, and the mass ratio of silicon micropowder to alumina is 0.5:1.
[0060] Example 8
[0061] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of two-component cinnamic acid modified epoxy prepolymer added is 45g, the amount of thermal conductive filler added is 55g, and the mass ratio of silicon micropowder and alumina is 1:1.
[0062] Example 9
[0063] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of two-component cinnamic acid modified epoxy prepolymer added is 45g, the amount of thermal conductive filler added is 55g, and the mass ratio of silicon micropowder to alumina is 0.25:1.
[0064] Example 10
[0065] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of two-component cinnamic acid modified epoxy prepolymer added is 45g, the amount of thermal conductive filler added is 55g, and the mass ratio of silicon micropowder to alumina is 0.5:1.
[0066] Embodiment 11
[0067] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of two-component cinnamic acid modified epoxy prepolymer added is 55g, the amount of thermal conductive filler added is 45g, and the mass ratio of silicon micropowder and alumina is 1:1.
[0068] Example 12
[0069] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of two-component cinnamic acid modified epoxy prepolymer added is 55 g, the amount of thermal conductive filler added is 45 g, and the mass ratio of silicon micropowder to alumina is 0.25:1.
[0070] Example 13
[0071] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of two-component cinnamic acid modified epoxy prepolymer added is 55g, the amount of thermal conductive filler added is 45g, and the mass ratio of silicon micropowder to alumina is 0.5:1.
[0072] Comparative Example 1
[0073] In this comparative example, a two-component UV-curable acrylic-epoxy resin film is prepared, which is the same as Example 2, except that the amount of thermal conductive filler (silicon powder) added in step 4 is 75 g.
[0074] Comparative Example 2
[0075] This comparative example prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of the two-component cinnamic acid modified epoxy prepolymer added is 35 g, and the amount of the thermal conductive filler (silicon powder) added is 65 g.
[0076] Comparative Example 3
[0077] This comparative example prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of the two-component cinnamic acid modified epoxy prepolymer added is 45g, and the amount of the thermal conductive filler (silicon powder) added is 55g.
[0078] Comparative Example 4
[0079] This comparative example prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of the two-component cinnamic acid modified epoxy prepolymer added is 55g, and the amount of the thermal conductive filler (silicon powder) added is 45g.
[0080] Comparative Example 5
[0081] In this comparative example, a two-component UV-curable acrylic-epoxy resin film is prepared, which is the same as Example 2, except that the amount of thermal conductive filler (aluminum oxide) added in step 4 is 75 g.
[0082] Comparative Example 6
[0083] This comparative example prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of the two-component cinnamic acid modified epoxy prepolymer added is 35 g, and the amount of the thermal conductive filler (aluminum oxide) added is 65 g.
[0084] Comparative Example 7
[0085] This comparative example prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of the two-component cinnamic acid modified epoxy prepolymer added is 45g, and the amount of the thermal conductive filler (aluminum oxide) added is 55g.
[0086] Comparative Example 8
[0087] This comparative example prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 2, except that in step 4, the amount of the two-component cinnamic acid modified epoxy prepolymer added is 55g, and the amount of the thermal conductive filler (aluminum oxide) added is 45g.
[0088] It can be seen from Table 2 that the increase of alumina content can significantly improve the overall thermal conductivity of the composite film material. Compared with a single filler, the addition of composite fillers increases the breakdown voltage and improves the toughness of the film.
[0089] Table 2 Effect of filler ratio and dosage on thermal conductivity
[0090]
[0091] Embodiment 14
[0092] This embodiment provides a method for preparing a two-component UV-curable acrylic-epoxy resin film, comprising the following steps:
[0093] Step 1, using sodium hydroxide as a catalyst, weighing 0.1 g of sodium hydroxide and dissolving it in 10 mL of ethanol solution, adding the dissolved sodium hydroxide solution to a mixed solution of 45 g of hydroxyl-terminated epoxy resin and 25 g of epoxy diluent to carry out a chemical ring-opening reaction, the reaction temperature is 75° C., the reaction time is 2 hours, and the ring-opened bisphenol A epoxy resin glue is obtained;
[0094] Step 2, adding 7 g of 3-phenyl-2-acrylic acid (cinnamic acid) to 45 g of the ring-opened bisphenol A epoxy resin glue obtained in step 1 at room temperature, and then placing the mixture in a heating jacket to heat the mixture for esterification reaction at a temperature of 110° C. for 3 hours to obtain a cinnamic acid-modified bisphenol A epoxy resin glue;
[0095] Step 3, adding 3g of ultraviolet light initiator, 15g of epoxy curing agent, 0.5g of accelerator and 0.1g of leveling agent to 45g of the cinnamic acid-modified bisphenol A epoxy resin glue prepared in step 2 under a light-proof environment, and stirring at room temperature for 0.5 hour to obtain a two-component cinnamic acid-modified epoxy prepolymer glue that can be photocured and heat-cured;
[0096] Step 4, add 2g of coupling agent to the configured two-component cinnamic acid modified epoxy prepolymer glue and disperse it at high speed for 5 minutes at a speed of 650rmp / min, quickly add 65g of weighed thermal conductive filler (silicon powder: alumina mass ratio of 0.25:1) and fully disperse it to obtain a two-component UV-curable acrylic-epoxy resin composite. The two-component UV-curable acrylic-epoxy resin composite is coated on the release film by a coating apparatus (the coating parameters of the coating machine are: coating in the dip tank, the coating speed is 0.5 m / min, the coating drying tunnel temperature is 90°C, and the drying tunnel length is 6 meters), and irradiate for 30s under ultraviolet light (290nm) for rapid curing and film formation, wherein the irradiation is carried out at room temperature to obtain a semi-cured bisphenol A film with uniform phase distribution.
[0097] Embodiment 15
[0098] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 14, except that in step 4, the mass ratio of silicon powder:alumina is 1:1.
[0099] Example 16
[0100] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 14, except that in step 4, the mass ratio of silicon powder:alumina is 0.5:1.
[0101] Embodiment 17
[0102] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 14, except that the amount of thermal conductive filler added in step 4 is 75 g, and the mass ratio of silicon micropowder:alumina is 1:1.
[0103] Embodiment 18
[0104] This embodiment prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 14, except that the amount of thermal conductive filler added in step 4 is 75 g, and the mass ratio of silicon micropowder:alumina is 0.25:1.
[0105] Comparative Example 9
[0106] This comparative example prepares a two-component UV-curable acrylic-epoxy resin film, which is the same as Example 14, except that the amount of thermal conductive filler (aluminum oxide) added in step 4 is 45 g.
[0107] Comparative Example 10
[0108] In this comparative example, a two-component UV-curable acrylic-epoxy resin film is prepared, which is the same as Example 14, except that the amount of thermal conductive filler (silicon powder) added in step 4 is 55 g.
[0109] The UV-cured composite adhesive film (i.e., semi-cured bisphenol A film) and copper foil prepared by Examples 14-18 and Comparative Examples 9-10 were pressed at 190° C. and 5 MPa for 2 hours to obtain an insulating composite copper foil, the properties of which are shown in Table 3.
[0110] Table 3 Properties of copper foil prepared by acrylic-epoxy resin film
[0111]
[0112] It can be seen from Table 3 that when the mass ratio of hollow silicon powder to alumina is 1:1, the dielectric loss of the copper clad laminate can reach less than 3 / 1000, which meets the attenuation problem of signal transmission under high frequency (5G, 6G); in addition, the amount of epoxy resin and filler are closely related to the peeling strength. The larger the epoxy resin and the filler dosage is at 65%, the higher the peeling strength between the film and the copper foil, and the better the electrical properties.
[0113] The breakdown voltage of the film prepared with composite fillers is increased, and the dielectric loss is significantly reduced. The prepared film has good toughness. It can withstand 288℃ soldering for up to 320 minutes, while the temperature resistance of a single filler is less than 20 minutes.
[0114] Embodiment 19
[0115] This embodiment provides a method for preparing a two-component UV-curable acrylic-epoxy resin film, comprising the following steps:
[0116] Step 1, using sodium hydroxide as a catalyst, weighing 0.2g of sodium hydroxide and dissolving it in 10mL of ethanol solution, adding the dissolved sodium hydroxide solution to a mixed solution of 50g of hydroxyl-terminated epoxy resin and 25g of epoxy diluent to carry out a chemical ring-opening reaction, the reaction temperature is 65°C, the reaction time is 2 hours, and the ring-opened bisphenol A epoxy resin glue is obtained;
[0117] Step 2, adding 10 g of 3-phenyl-2-acrylic acid (cinnamic acid) to 50 g of the ring-opened bisphenol A epoxy resin glue prepared in step 1 at room temperature, and then placing it in a heating jacket to heat up for esterification reaction, the reaction temperature is 90° C., the reaction time is 2 hours, and the cinnamic acid-modified bisphenol A epoxy resin glue is obtained;
[0118] Step 3, adding 5g of ultraviolet light initiator, 10g of epoxy curing agent, 1g of accelerator and 0.05g of leveling agent to 50g of the cinnamic acid modified bisphenol A type epoxy resin glue prepared in step 2 under a light-proof environment, and stirring at room temperature for 0.5 hours to obtain a two-component cinnamic acid modified epoxy prepolymer glue that can be photocured and heat-cured;
[0119] Step 4: Add 2g of coupling agent to the prepared two-component cinnamic acid modified epoxy prepolymer glue and disperse it at high speed for 5 minutes at a speed of 650rmp / min, and quickly add 75g of thermal conductive filler (the mass ratio of silicon micropowder and alumina is 0.5:1) to fully disperse it evenly to obtain a two-component UV-curable acrylic-epoxy resin composite. The two-component UV-curable acrylic-epoxy resin composite is coated on the release film by a coating apparatus (the coating parameters of the coating machine are: coating in the dipping tank, the coating speed is 0.5 m / min, the coating drying tunnel temperature is 90°C, and the drying tunnel length is 6 meters), and irradiate under ultraviolet light (290nm) for 30s to quickly cure and form a film, wherein the irradiation is carried out at room temperature to obtain a semi-cured bisphenol A film with uniform phase distribution.
[0120] The prepared UV-cured composite adhesive film (i.e., semi-cured bisphenol A film) and copper foil were pressed at 170° C. and 10 MPa for 2 hours to obtain an insulating composite copper foil.
[0121] Embodiment 20
[0122] This embodiment provides a method for preparing a two-component UV-curable acrylic-epoxy resin film, comprising the following steps:
[0123] Step 1, using sodium hydroxide as a catalyst, weighing 0.3 g of sodium hydroxide and dissolving it in 10 mL of ethanol solution, adding the dissolved sodium hydroxide solution to a mixed solution of 55 g of hydroxyl-terminated epoxy resin and 25 g of epoxy diluent to carry out a chemical ring-opening reaction, the reaction temperature is 75° C., the reaction time is 2.5 hours, and the ring-opened bisphenol A epoxy resin glue is obtained;
[0124] Step 2, adding 12g of 3-phenyl-2-acrylic acid (cinnamic acid) to 55g of the ring-opened bisphenol A epoxy resin glue prepared in step 1 at room temperature, and then placing it in a heating jacket to heat up for esterification reaction, the reaction temperature is 85°C, the reaction time is 2.5 hours, and the cinnamic acid-modified bisphenol A epoxy resin glue is obtained;
[0125] Step 3, adding 5g of ultraviolet light initiator, 5g of epoxy curing agent, 1.65g of accelerator and 0.165g of leveling agent to 55g of the cinnamic acid-modified bisphenol A epoxy resin glue prepared in step 2 under a light-proof environment, and stirring at room temperature for 0.5 hour to obtain a two-component cinnamic acid-modified epoxy prepolymer glue that can be photocured and heat-cured;
[0126] Step 4: Add 2g of coupling agent to the prepared two-component cinnamic acid modified epoxy prepolymer glue and disperse it at high speed for 5 minutes at a speed of 650rmp / min, and quickly add 75g of thermal conductive filler (the mass ratio of silicon micropowder and alumina is 0.5:1) to fully disperse it evenly to obtain a two-component UV-curable acrylic-epoxy resin composite. The two-component UV-curable acrylic-epoxy resin composite is coated on the release film by a coating apparatus (the coating parameters of the coating machine are: coating in the dipping tank, the coating speed is 0.5 m / min, the coating drying tunnel temperature is 90°C, and the drying tunnel length is 6 meters), and irradiate under ultraviolet light (290nm) for 30s to quickly cure and form a film, wherein the irradiation is carried out at room temperature to obtain a semi-cured bisphenol A film with uniform phase distribution.
[0127] The prepared UV-cured composite adhesive film (i.e., semi-cured bisphenol A film) and copper foil were pressed at 220° C. and 5 MPa for 2 hours to obtain an insulating composite copper foil.
[0128] Embodiment 21
[0129] This embodiment provides a method for preparing a two-component UV-curable acrylic-epoxy resin film, comprising the following steps:
[0130] Step 1, using sodium hydroxide as a catalyst, weighing 0.3 g of sodium hydroxide and dissolving it in 10 mL of ethanol solution, adding the dissolved sodium hydroxide solution to a mixed solution of 60 g of hydroxyl-terminated epoxy resin and 25 g of epoxy diluent to carry out a chemical ring-opening reaction, the reaction temperature is 70° C., the reaction time is 2 hours, and the ring-opened bisphenol A epoxy resin glue is obtained;
[0131] Step 2, adding 12 g of 3-phenyl-2-acrylic acid (cinnamic acid) to 60 g of the ring-opened bisphenol A epoxy resin glue prepared in step 1 at room temperature, and then placing it in a heating jacket to heat up for esterification reaction, the reaction temperature is 90° C., the reaction time is 1.5 hours, and a cinnamic acid-modified bisphenol A epoxy resin glue is obtained;
[0132] Step 3, adding 2g of ultraviolet initiator, 5g of epoxy curing agent, 2.4g of accelerator and 0.12g of leveling agent to 60g of the cinnamic acid modified bisphenol A type epoxy resin glue prepared in step 2 under a light-proof environment, and stirring at room temperature for 0.5 hour to obtain a two-component cinnamic acid modified epoxy prepolymer glue that can be photocured and heat-cured;
[0133] Step 4: Add 2g of coupling agent to the prepared two-component cinnamic acid modified epoxy prepolymer glue and disperse it at high speed for 5 minutes at a speed of 650rmp / min, and quickly add 75g of thermal conductive filler (the mass ratio of silicon micropowder and alumina is 0.5:1) to fully disperse it evenly to obtain a two-component UV-curable acrylic-epoxy resin composite. The two-component UV-curable acrylic-epoxy resin composite is coated on the release film by a coating apparatus (the coating parameters of the coating machine are: coating in the dipping tank, the coating speed is 0.5 m / min, the coating drying tunnel temperature is 90°C, and the drying tunnel length is 6 meters), and irradiate under ultraviolet light (290nm) for 30s to quickly cure and form a film, wherein the irradiation is carried out at room temperature to obtain a semi-cured bisphenol A film with uniform phase distribution.
[0134] The prepared UV-cured composite adhesive film (i.e., semi-cured bisphenol A film) and copper foil were pressed at 180° C. and 7 MPa for 2 hours to obtain an insulating composite copper foil.
[0135] Embodiment 22
[0136] This embodiment provides a method for preparing a two-component UV-curable acrylic-epoxy resin film, comprising the following steps:
[0137] Step 1, using potassium hydroxide as a catalyst, weighing 0.5g of sodium hydroxide and dissolving it in 10mL of ethanol solution, adding the dissolved potassium hydroxide solution into a mixed solution of 70g of hydroxyl-terminated epoxy resin and 25g of epoxy diluent to carry out a chemical ring-opening reaction, the reaction temperature is 60°C, the reaction time is 1 hour, and the ring-opened bisphenol A epoxy resin glue is obtained;
[0138] Step 2, adding 15 g of 3-phenyl-2-acrylic acid (cinnamic acid) to 70 g of the ring-opened bisphenol A epoxy resin glue prepared in step 1 at room temperature, and then placing it in a heating jacket to heat up for esterification reaction, the reaction temperature is 75° C., the reaction time is 2 hours, and the cinnamic acid-modified bisphenol A epoxy resin glue is obtained;
[0139] Step 3, adding 2g of ultraviolet light initiator, 5g of epoxy curing agent, 3.5g of accelerator and 0.20g of leveling agent to 70g of the cinnamic acid modified bisphenol A type epoxy resin glue prepared in step 2 under a light-proof environment, and stirring at room temperature for 1.5 hours to obtain a two-component cinnamic acid modified epoxy prepolymer glue that can be photocured and heat-cured;
[0140] Step 4: Add 2g of coupling agent to the prepared two-component cinnamic acid modified epoxy prepolymer glue and disperse it at high speed for 5 minutes at a speed of 650rmp / min, and quickly add 75g of thermal conductive filler (the mass ratio of silicon micropowder and alumina is 0.5:1) to fully disperse it evenly to obtain a two-component UV-curable acrylic-epoxy resin composite. The two-component UV-curable acrylic-epoxy resin composite is coated on the release film by a coating apparatus (the coating parameters of the coating machine are: coating in the dipping tank, the coating speed is 0.5 m / min, the coating drying tunnel temperature is 90°C, and the drying tunnel length is 6 meters), and irradiate under ultraviolet light (290nm) for 30s to quickly cure and form a film, wherein the irradiation is carried out at room temperature to obtain a semi-cured bisphenol A film with uniform phase distribution.
[0141] The prepared UV-cured composite adhesive film (i.e., semi-cured bisphenol A film) and copper foil were pressed at 190° C. and 5 MPa for 2 hours to obtain an insulating composite copper foil.
[0142] Embodiment 23
[0143] This embodiment provides a method for preparing a two-component UV-curable acrylic-epoxy resin film, comprising the following steps:
[0144] Step 1, using sodium hydroxide as a catalyst, weighing 0.5 g of sodium hydroxide and dissolving it in 10 mL of ethanol solution, adding the dissolved barium hydroxide solution to a mixed solution of 75 g of hydroxyl-terminated epoxy resin and 25 g of epoxy diluent to carry out a chemical ring-opening reaction, the reaction temperature is 65° C., the reaction time is 1.5 hours, and the ring-opened bisphenol A epoxy resin glue is obtained;
[0145] Step 2, adding 15g of 3-phenyl-2-acrylic acid (cinnamic acid) to 75g of the ring-opened bisphenol A epoxy resin glue prepared in step 1 at room temperature, and then placing it in a heating jacket to heat up for esterification reaction, the reaction temperature is 85°C, the reaction time is 2 hours, and the cinnamic acid-modified bisphenol A epoxy resin glue is obtained;
[0146] Step 3, adding 2g of ultraviolet light initiator, 5g of epoxy curing agent, 2.25g of accelerator and 0.075g of leveling agent to 75g of the cinnamic acid-modified bisphenol A epoxy resin glue prepared in step 2 under a light-proof environment, and stirring at room temperature for 1.5 hours to obtain a two-component cinnamic acid-modified epoxy prepolymer glue that can be photocured and heat-cured;
[0147] Step 4: Add 2g of coupling agent to the prepared two-component cinnamic acid modified epoxy prepolymer glue and disperse it at high speed for 5 minutes at a speed of 650rmp / min, and quickly add 75g of thermal conductive filler (the mass ratio of silicon micropowder and alumina is 0.5:1) to fully disperse it evenly to obtain a two-component UV-curable acrylic-epoxy resin composite. The two-component UV-curable acrylic-epoxy resin composite is coated on the release film by a coating apparatus (the coating parameters of the coating machine are: coating in the dipping tank, the coating speed is 0.5 m / min, the coating drying tunnel temperature is 90°C, and the drying tunnel length is 6 meters), and irradiate under ultraviolet light (290nm) for 30s to quickly cure and form a film, wherein the irradiation is carried out at room temperature to obtain a semi-cured bisphenol A film with uniform phase distribution.
[0148] The prepared UV-cured composite adhesive film (i.e., semi-cured bisphenol A film) and copper foil were pressed at 190° C. and 5 MPa for 2 hours to obtain an insulating composite copper foil.
[0149] Compared with the insulating dielectric film prepared by Li Huilu et al. in "Development of High-heat Insulating Dielectric Film for Metal Substrates" published in "Insulating Materials", the present invention effectively improves the breakdown voltage and reduces the dielectric loss after modifying the epoxy resin. The loss can be less than 3 thousandths, and the soldering resistance at 288°C can exceed 4 hours.
[0150] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0151] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a two-component UV-curable acrylic-epoxy resin film, characterized in that: Prepared according to the following steps: Step 1, using an alkali agent as a catalyst, a hydroxyl-terminated epoxy resin and an epoxy diluent undergo a chemical ring-opening reaction to obtain an epoxy resin glue solution after ring opening; the reaction temperature of the chemical ring-opening reaction is 60-75° C., and the reaction time is 1-2.5 hours; wherein the mass ratio of the hydroxyl-terminated epoxy resin, the epoxy diluent, and the alkali agent is 45-75:25:0.1-1.5; and the hydroxyl-terminated epoxy resin is GEBR481A80 epoxy resin; Step 2, adding 3-phenyl-2-acrylic acid to the ring-opened epoxy resin prepared in step 1 to carry out an esterification reaction to obtain a cinnamic acid-modified epoxy resin glue; the reaction temperature of the esterification reaction is 75-90° C., and the reaction time is 1.5-3 hours; wherein the molar ratio of the carboxyl group of 3-phenyl-2-acrylic acid to the epoxy group in the ring-opened epoxy resin glue is 0.15-0.55:1; Step 3, adding an ultraviolet light initiator, an epoxy curing agent, an accelerator and a leveling agent to the cinnamic acid-modified epoxy resin prepared in step 2, and mixing them evenly at room temperature in the dark to obtain a two-component cinnamic acid-modified epoxy prepolymer glue; Step 4: Add the coupling agent and the thermal conductive filler to the two-component cinnamic acid modified epoxy prepolymer prepared in step 3 and disperse them evenly to obtain a two-component UV-curable acrylic-epoxy resin composite adhesive solution, which is coated on a release film, and cured under ultraviolet light to obtain a semi-cured two-component UV-curable acrylic-epoxy resin adhesive film; the mass ratio of the coupling agent, the thermal conductive filler, and the two-component cinnamic acid modified epoxy prepolymer is 1-3:65-75:25-45; the thermal conductive filler is a composite of silicon micropowder and alumina, and the mass ratio of silicon micropowder to alumina is 0.5-1:1; and the release film is a polyethylene glycol film.
2. The method for preparing a two-component UV-curable acrylic-epoxy resin film according to claim 1, characterized in that: In step 1, the alkaline agent is one of potassium hydroxide, barium hydroxide or sodium hydroxide.
3. The method for preparing a two-component UV-curable acrylic-epoxy resin film according to claim 1, characterized in that: In step 3, the mass ratio of the ultraviolet light initiator to the cinnamic acid modified epoxy resin glue is 0.06-0.1:1; the mass ratio of the epoxy curing agent to the cinnamic acid modified epoxy resin is 0.04-0.3:1; the mass ratio of the accelerator to the cinnamic acid modified epoxy resin is 0.01-0.05:1; the mass ratio of the leveling agent to the cinnamic acid modified epoxy resin is 0.001-0.003:
1.
4. The method for preparing a two-component UV-curable acrylic-epoxy resin film according to claim 1, characterized in that: In step 3, the ultraviolet light initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, the epoxy curing agent is bismaleimide, the accelerator is 2-ethyl-4-methylimidazole and the leveling agent is polyether-modified siloxane.
5. A two-component UV-curable acrylic-epoxy resin film prepared by the preparation method according to any one of claims 1 to 4.
6. Application of the two-component UV-curable acrylic-epoxy resin film according to claim 5 in PCB board material, characterized in that: After the two-component UV-curable acrylic-epoxy resin film is laminated with the copper foil, secondary high-temperature curing is performed to obtain a PCB board; Among them, the secondary high-temperature curing temperature is 170-220°C, the curing time is 2h, and the press pressure is 5-10Mpa.
Citation Information
Patent Citations
High purity photo-thermal curing adhesive and preparation method thereof
CN101654607A